Karnataka - A Rapid Private Health Sector Assessment - World Bank (Washington, DC: World Bank, 2022)
This paper presents a rapid private health sector assessment for Karnataka. Karnataka is a middle-tier Indian state with most state-wide health indicators mirroring those for the nation as a whole. In addition to these health statistics, more than half of Karnataka's children suffer from malnutrition. Improving primary health care services is a key to improving these health indicators. Improving health outcomes will depend on improving the quality, outreach and responsiveness of primary health care providers. Government can consider scaling up the successful experiences of community health care financing. More specifically the findings of this study and the discussion that it engenders will be used to inform the design of the proposed Karnataka Health Nutrition and Population (HNP) project. Karnataka currently has 1,685 Primary Health Center's (PHCs) and 583 Primary Health Units (PHUs). The PHC is intended to serve a population of 30,000 with smaller populations in the more remote rural or hilly areas and larger populations covered in urban areas. It is reported that the PHCs are not currently able to fulfill all these functions, many of which have a strong public good component. As such, the private sector can still play a role in delivering these services, although they will have to be funded by the public sector. Some services will have a mixture of public and private good characteristics, while others will be purely private goods. It is the latter group of services that are most amenable to privately-funded, privately provided health care. In general, the public health care system is managed and overseen by the district health officers. Although they are qualified doctors, they have little or no training in public health management and are transferred frequently. Moreover, even if they had the training they do not have the flexibility to reallocate financial, capital and human resources to achieve better outcomes.